PELATIHAN MENGELOLA DAFTAR PUSTAKA MENGGUNAKAN APLIKASI MENDELEY PADA MUSYAWARAH GURU MATA PELAJARAN (MGMP) BAHASA INDONESIA SMA/SMK KOTA BENGKULU - Yanti, Nafri; Setiawan, Yudi; Rini, Dyah Setyo (Jurnal Berdaya Mandiri, 2020)
The Mendeley application training at the MGMP Bahasa Indonesia SMA/SMK in Bengkulu City aims to improve the knowledge and skills of the teacher using the Mendeley application, as well as facilitate management and library writing. This activity is carried out using several methods, namely observation/monitoring, interviews, and questionnaires. The results of this training activity can be used as one of the learning media for the preparation of bibliography, so this activity is not only useful for teachers, but also students taught by teachers in their respective work units. In addition, this activity can increase the ability of teachers to write scientific articles, especially in compiling and managing bibliography. Based on the data, this training adds to the insights of teachers in managing libraries and is able to apply this application in teaching and learning in their respective schools.